The Analysis of Protein Content, Iron Content, and Acceptability of Crackers Substituted with Edamame (Glycine max L. Merrill) Flour and Mackerel Tuna (Euthynnus affinis) Protein Hydrolysate - Septi Nur Rachmawati; Maulina Sefi Astuti; Leersia Yusi Ratnawati (Window of Health : Jurnal Kesehatan, 2025)
Crackers are a snack often favored by toddlers. Commercially available crackers predominantly use wheat flour, which is high in carbohydrates but low in nutritional value, particularly in protein content. Therefore, innovative formulations are needed to enrich the nutrition, notably protein and iron, by substituting edamame flour and mackerel tuna protein hydrolysate into crackers to help address stunting. This study aims to analyze the protein content, iron content, and acceptability of crackers made with a substitution of edamame flour and tuna protein hydrolysate. This research was conducted at the University of Jember from February to April 2024 using a completely randomized design at four levels. Protein analysis used the Kjeldahl method, and iron content was examined by atomic absorption spectrometry. The acceptability was tested using the hedonic scale test on 30 semi-trained panelists. The results were analyzed using SPSSv24. Results showed statistically significant differences in protein content, iron content, color acceptability, aroma, and taste. The highest protein content is found in A3, while the highest iron content is found in A1. The best formulation, determined by the exponential comparison method, was treatment A2. In conclusion, substitution with edamame flour and tuna protein hydrolysate in all treatment variations significantly affected protein content, iron content, and acceptability in terms of color, aroma, and taste; however, it did not substantially impact texture or overall acceptability. Substitution of edamame flour and mackerel tuna protein hydrolysate in crackers can increase protein content and therefore could be an effective measure in preventing stunting.